Analysis of fiscal sustainability and its impact on enhancing economic growth in Iraq for the period (2004-2021) - Fadhal Hamad Al- Qaisy*, Omar; Yahiya Saleh Al- Kubaisi, Lawrence (Journal of Economics and Administrative Sciences, 2024)
The research aims to analyze and measure the reality of the Iraqi economy for the period (2004-2021)by applying the concept of financial sustainability and its indicators on economic growth. The paper’s problem lies in the weak implementation of financial sustainability and indicators in most financial decisions in Iraq, negatively impacting economic growth in most economic sectors in Iraq. The paper started from the hypothesis that the weak implementation of financial sustainability in most of Iraq has contributed to the weakness of economic growth. The validity of the hypothesis has been proven using a standard model known as the Multiple Regression Model (ARDL), the study has yielded several results, the most important being the inverse relationship between the budget deficit as an independent variable and economic growth as a dependent variable. The budget deficit reached (59%) of the "gross domestic Product" indicating a deviation from the 3% deficit defined by the Maastricht treaty to ensure deficit coverage. Iraq’s deviation from this percentage will lead to a decrease in economic growth. The paper also revealed an inverse relationship between public debt as an independent variable and economic growth as a dependent variable due to Iraq’s violation of the golden rule, which dictates allocating debt to the investment side rather than consumptive spending. Paper type: Research paper.